April blood : Florence and the plot against the Medici - Martines, Lauro (Oxford University Press, 2003)
One of the world's leading historians of Renaissance Italy brings to life here the vibrant--and violent--society of fifteenth-century Florence. His disturbing narrative opens up an entire culture, revealing the dark side of Renaissance man and politician Lorenzo de' Medici. On a Sunday in April 1478, assassins attacked Lorenzo and his brother as they attended Mass in the cathedral of Florence. Lorenzo scrambled to safety as Giuliano bled to death on the cathedral floor. April Blood moves outward in time and space from that murderous event, unfolding a story of tangled passions, ambition, treac.